THE DEVELOPMENT OF HERBAL MEDICINE PLANTATION PILOT DISTRICT THROUGH COMMUNITY EMPOWERMENT IN HARAPAN DISTRICT, PONDOK KELAPA - Herman Syah; Dahrizal Dahrizal; Hendri Heryanto; Andra Saferi Wijaya (Caring : Jurnal Pengabdian Masyarakat, 2021)
According to Riskesdas 2018, the proportion of toga utilization in Indonesia was 24.6%, while in Bengkulu Province it was around 42%. From the research results, it is known that the implementation of the TOGA program in this research area is still lacking. This is partly because people do not know about the benefits of family medicinal plants so that the use of yard land is still not optimal. The second reason is the absence of special officers at the puskesmas who manage the activities of planting medicinal plants. Based on interviews with the village head of Harapan, it was found that the low utilization of the home page, garden or fields used to cultivate medicinal plants in order to meet family needs and the lack of community knowledge about family medicinal plants indicate that there was still a lack of socialization about family medicinal plants to health cadres as spearhead of health workers in conveying information and providing guidance to families and communities. The purpose of this community service activity is to develop a toga village in Harapan Village, Pondok Kelapa District, Central Bengkulu Regency by empowering families through Health Cadres. The method used in the implementation of the activity is using the concept of community nursing and family nursing (Family and Community Nursing Aproach) and using the Community Development (CD), Persuasive and Educational model. The results of the socialization showed that there was an increase in the knowledge of PKK cadres after participated in the socialization about family medicinal plants and simple medicine from Toga (p : 0.006), a demonstration toga was formed in the Harapan Village office yard and the residents' home page. The conclusion of this activity is that 2 family medicinal plant gardens have been formed in the village office yard and the residents' home page as a model robe for the local residents. It is hoped that residents can make gowns in their respective yards so that they become a source of simple medicine and first aid if there are people who are sick community.